Effects of infection with the viral complex alfalfa dwarf disease on productivity traits and coumestrol production in alfalfa plants - Silva, Mercedes Pilar; Basigalup, Daniel Horacio; Chiacchiera, Stella Maris; Trucco, Veronica Milagros; Giolitti, Fabian; Mamani, Eva Maria Celia; Díaz, Carolina del Pilar; Manzur, Milena E. (CSIRO, 2023)
Programa de capacitación y perfeccionamiento, Resolución 1029/2012. Financiación de ANPCyT BID PICT 2017-3594